A longitudinal qualitative study on the care needs journey map of primary caregivers of patients undergoing total knee arthroplasty - Hu, Jingru; Dong, Guanglei; Liu, Dongfang; Wang, Dongyang (Frontiers in Rehabilitation Sciences, 2025)
BackgroundTotal knee arthroplasty (TKA) is a common and effective treatment for advanced knee osteoarthritis, yet it imposes significant demands on primary caregivers throughout the perioperative and rehabilitation phases. Understanding caregivers’ evolving needs is critical for optimizing patient outcomes and sustaining caregiver well-being. This study aimed to explore the dynamic care experiences and changing needs of primary caregivers of TKA patients across three distinct phases: the diagnosis period, discharge transition, and rehabilitation phase, and to construct a comprehensive journey map of caregiving needs.MethodsA longitudinal qualitative study was conducted using purposive sampling. Sixteen primary caregivers of patients undergoing unilateral TKA were recruited from a tertiary hospital in Henan, China. Semi-structured interviews were conducted at three time points: preoperative (T1), pre-discharge (T2), and one month post-discharge (T3), resulting in 43 interviews. Data were analyzed using content analysis and synchronized temporal mapping to identify themes and subthemes along the caregiving timeline.ResultsFour major themes and 27 subthemes were identified: care tasks, emotional experiences, caregiving barriers, and support systems. Caregivers’ responsibilities evolved from pre-surgical information gathering to intensive post-surgical care and long-term rehabilitation support. Emotional burdens shifted from anxiety and helplessness to fatigue and psychological strain. Major barriers included knowledge deficits, skill limitations, and inadequate systemic support. The caregiver support network transitioned from hospital-based to community and family-based systems over time. A visual journey map was developed to represent these findings.ConclusionPrimary caregivers of TKA patients face complex and changing needs across different stages of care. A caregiver-centered, multidisciplinary, and phase-specific support framework is essential to improve the quality of postoperative care and reduce caregiver burden.